2019
DOI: 10.1177/0954410019831198
|View full text |Cite
|
Sign up to set email alerts
|

Design of a conflict-detection air traffic control tool for the implementation of continuous climb operations: A case study at Palma TMA

Abstract: Continuous climb operation is an operational concept that allows airlines to perform an optimal departing trajectory avoiding air traffic control segregation requirements. This concept implies the design and integration of air traffic flows for the sake of safety performance. This paper designs a new conflict-detection air traffic control tool based on the blocking-area concept, characterises the conflict probability between air traffic flows and assesses the impact of continuous climb operation integration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Paielli et al [14] developed a new approach based on tactical pairwise trajectory analysis. Other authors found their studies on complex probabilistic models to understand trajectory uncertainty [15][16][17][18].…”
Section: Of 18mentioning
confidence: 99%
“…Paielli et al [14] developed a new approach based on tactical pairwise trajectory analysis. Other authors found their studies on complex probabilistic models to understand trajectory uncertainty [15][16][17][18].…”
Section: Of 18mentioning
confidence: 99%
“…Paielli et al [ 18 ] developed a new approach based on tactical pairwise trajectory analysis. Other authors found their studies on complex probabilistic models to understand trajectory uncertainty [ 19 , 20 , 21 ].…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…The blocking-area allows knowing if an aircraft influences the trajectory of other aircraft and may imply a modification of the other trajectory. When the blocking-area transforms its application from location to time, it evolves to a temporary-blocking window [24][25][26]. In this case, the temporary-blocking window provides the time span an aircraft cannot enter in the critical section because one conflict will arise.…”
Section: Introductionmentioning
confidence: 99%